2006
DOI: 10.1063/1.2345202
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effects in the CO dimer: Millimeter wave spectrum and rovibrational calculations of (C12O18)2

Abstract: The millimeter wave spectrum of the isotopically substituted CO dimer, (12C18O)2, was studied with the Orotron jet spectrometer, confirming and extending a previous infrared study [A. R. W. McKellar, J. Mol. Spectrosc. 226, 190 (2004)]. A very dilute gas mixture of CO in Ne was used, which resulted in small consumption of 12C18O sample gas and produced cold and simple spectra. Using the technique of combination differences together with the data from the infrared work, six transitions in the 84-127 GHz region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The agreement is similarly good as it was for the lower states of ( 12 C 16 O) 2 observed previously and for the isotopologues ( 13 C 16 O) 2 and ( 12 C 18 O) 2 . 24,26 This shows that the hybrid potential constructed in ref 26 is very accurate indeed.…”
Section: Rovibrational Calculationsmentioning
confidence: 65%
See 1 more Smart Citation
“…The agreement is similarly good as it was for the lower states of ( 12 C 16 O) 2 observed previously and for the isotopologues ( 13 C 16 O) 2 and ( 12 C 18 O) 2 . 24,26 This shows that the hybrid potential constructed in ref 26 is very accurate indeed.…”
Section: Rovibrational Calculationsmentioning
confidence: 65%
“…13,[20][21][22][23][24] There has also been parallel progress in accurate ab initio calculations of a reliable potential energy surface combined with calculations of the rovibrational states of the dimer. 25,26 The experimental results for ( 12 C 16 O) 2 2 isotopologues in ref 24. The last paper gives also an extensive description of the current understanding of the structure and dynamics of the CO dimer based on a recently developed hybrid potential from ab initio coupled cluster [CCSD(T)] and symmetry-adapted perturbation theory (DFT-SAPT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The complexes N 2 –N 2 , CO–N 2 , and CO–CO thus form a family of dimers with interesting similarities as well as obvious differences. Since it lacks a permanent dipole moment, the N 2 dimer is relatively inaccessible by spectroscopy and has only been observed at pressures (1 atm) and temperatures (77 K) that do not allow high spectral resolution. , Spectra of CO dimer were first successfully assigned around the same time as those of CO–N 2 , , and there has been considerable further progress, as summarized in very recent experimental and theoretical papers. CO dimer can be thought of as having two isomers with almost equal binding energies.…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4 of Ref. [5], can only be explained by a considerable, mass-dependent, amount of tunneling between the two nearly isoenergetic ''isomers". Yamada [1] writes: ''Because the vibrational symmetry of the a and c states is the same, these states cannot be the components of a tunneling pair".…”
mentioning
confidence: 96%
“…Surin et al [2][3][4][5] have shown in a series of combined experimental and theoretical studies of different isotopologues of the CO dimer that this complex is extremely floppy. It has intermolecular vibrations with large amplitudes and the frequency of the lowest mode, the geared bend vibration, is only 3.7 cm À1 .…”
mentioning
confidence: 96%